2022
DOI: 10.1002/jgc4.1579
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and training needs of oncologists and surgeons in mainstreaming breast cancer genetic counseling in a low‐to‐middle income Asian country

Abstract: With the advent of poly‐ADP‐ribose polymerase inhibitor (PARPi) therapies, the focus of genetic testing for breast, ovarian, and other cancers has shifted from risk management to treatment decision‐making in high‐resource settings. Due to the shortage of genetic counselors worldwide, alternative ways of delivering genetic counseling have been explored, including training nongenetics healthcare professionals (NGHPs) to provide genetic counseling. However, little is known about the feasibility of adopting such m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…shown conflicting results, with both HCPs having a positive attitude toward mainstream GT, 17,18,24 but also expressing concern about their ability to provide adequate pre-test GC. 13,19,21 A possible explanation for the positive attitude and high participation rate in our training is the close involvement of HCPs in shaping our new pathway. This allowed them to raise concerns and consider the new pathway.…”
Section: Attitudes Perceived Knowledge Self-efficacy and Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…shown conflicting results, with both HCPs having a positive attitude toward mainstream GT, 17,18,24 but also expressing concern about their ability to provide adequate pre-test GC. 13,19,21 A possible explanation for the positive attitude and high participation rate in our training is the close involvement of HCPs in shaping our new pathway. This allowed them to raise concerns and consider the new pathway.…”
Section: Attitudes Perceived Knowledge Self-efficacy and Knowledgementioning
confidence: 99%
“…This is notable, because previous research into mainstream GT in breast cancer care has shown significant involvement of oncologists between 30 and 100%, probably due to differences in care pathways. 19,[34][35][36][37] In our study, patients eligible for GT were initially seen by the surgical team. However, the importance of GT by medical oncologists is expected to increase due to the rise of PARP-inhibiting therapies in carriers of germline BRCA1/2 pathogenic variants.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Similar access issues are seen in Southeast Asia. [6][7][8] Disparate access to these technologies in the low-and middle-income countries of Africa and Asia is especially alarming in the context of their disproportionately rising rates of breast cancer, with much of these increases experienced by younger/premenopausal women. Data on agestandardized breast cancer incidence demonstrate the highest burden of diagnoses among premenopausal-aged women in sub-Saharan Africa and in Southeast Asia relative to other regions of the world.…”
mentioning
confidence: 99%
“…Despite frequency of triple-negative breast cancer (a documented risk factor for BRCA mutation-related hereditary cancer susceptibility) being notably higher in western sub–Saharan African women, population-based data on BRCA mutation carrier status are sparse because of testing costs and a lack of genetic counseling services . Similar access issues are seen in Southeast Asia …”
mentioning
confidence: 99%